Angiopoietin 2 as a Novel Potential Biomarker for Acute Aortic Dissection - Huang, Bi; Tian, Li; Chen, Zhaoran; Zhang, Liang; Su, Wenjun; Lu, Tianyi; Yang, Yanmin; Hui, Rutai; Wang, Xiaojian; Fan, Xiaohan (Frontiers in Cardiovascular Medicine, 2021)
Biomarker-assisted diagnosis of acute aortic dissection (AAD) is important for initiation of treatment and improved survival. However, identification of biomarkers for AAD in blood is a challenging task. The present study aims to find the potential AAD biomarkers using a transcriptomic strategy. Arrays based genome-wide gene expression profiling were performed using ascending aortic tissues which were collected from AAD patients and healthy donors. The differentially expressed genes were validated using quantitative reverse transcriptase PCR (qRT-PCR) and western blot. The plasma levels of a potential biomarker, angiopoietin 2 (ANGPT2) were determined in case-control cohort (77 AAD patients and 82 healthy controls) by enzyme linked immunosorbent assay. Receiver operating characteristic curve (ROC) was used to evaluate the diagnostic power of ANGPT2 for AAD. Transcriptome data demonstrated that a total of 18 genes were significantly up-regulated and 28 genes were significantly down-regulated among AAD tissues (foldchange>3.0, p<0.01). By bioinformatic analysis, we identified ANGPT2 as a candidate biomarker for blood-based detection of AAD. The qRT-PCR and protein expression demonstrated that ANGPT2 increased 2.4- and 4.2 folds, respectively in aortic tissue of AAD patients. Immunohistochemical staining demonstrated that ANGPT2 was markedly increased in intima of the aortic wall in AAD. Furthermore, ANGPT2 was significantly elevated in AAD patients as compared with controls (median 1625 vs. 383 pg/ml, p <1E-6). ROC curve analysis showed that ANGPT2 was highly predictive of a diagnosis of type A AAD (area under curve 0.93, p < 1E-6). Sensitivity and specificity were 81% and 90%, respectively at the cutoff value of 833 pg/ml. In conclusion, ANGPT2 could be a promising biomarker for diagnosis of AAD; however, more studies are still needed to verify its specificity in diagnosing of AAD.